BIAYA EKSTERNAL DAN INTERNALISASI LIMBAH PABRIK KELAPA SAWIT - Rany Utami; Eka Intan Kumala Putri; Meti Ekayani (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
The product of waste water from the process of millers may cause externality. In order to prevent the externality, millers has to internalize it by developing an installation of waste water treatment. The current is not sufficient for treating whole waste from the CPO process, therefore, can generate externality and external costs to community. This study aims to estimate the external cost and propose three alternatives of alternative of internalizations. The result of the research shows that the external cost is 146,194,433 IDR/year. The alternative of internalization offered are; compensation cost payment, sludge pond recovery, and well development.